2017
DOI: 10.1080/10245332.2017.1414910
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the significance and health implications of asplenia in a cohort of patients with haemaglobinopathy: possible benefits of a spleen registry

Abstract: This study examined knowledge and attitudes about splenectomy in a cohort of haemoglobinopathy patients in an Australian tertiary referral centre. The majority had good or fair knowledge with a strong association of some elements of post-splenectomy care with being placed on a spleen registry and having received targeted education. Implementation of systematic approaches by medical staff is likely to be the main benefit of a clinical registry approach in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In another retrospective cohort study, Arnott A. et al concluded that systemic, long-term approaches can significantly minimize the risk of infection with encapsulated pathogens among splenectomized individuals [48]. According to Premawardena C et al, major benefits of the registry were not related to the knowledge but in the delivery of the recommended vaccines and the use of a medical alert card [49].…”
Section: Benefits Of Having a Spleen Registrymentioning
confidence: 99%
“…In another retrospective cohort study, Arnott A. et al concluded that systemic, long-term approaches can significantly minimize the risk of infection with encapsulated pathogens among splenectomized individuals [48]. According to Premawardena C et al, major benefits of the registry were not related to the knowledge but in the delivery of the recommended vaccines and the use of a medical alert card [49].…”
Section: Benefits Of Having a Spleen Registrymentioning
confidence: 99%
“… 6–8 Despite this, PWA/H are often managed inappropriately which leaves them exposed to unnecessary risk and speaks to a gap in knowledge translation. 9 Some work in this patient population has been previously done, 10 11 however, to our knowledge, the evaluation of a multimodal quality improvement intervention for both PWA/H and their healthcare providers has not previously been performed. We present the methodology employed in the development of this programme and the pilot data from a tertiary care centre that explored whether a medical alert card and patient/healthcare provider educational booklet increase vaccination rates and improve awareness and understanding of the infectious implications of a/hyposplenia in adults.…”
Section: Problemmentioning
confidence: 99%
“…A questionnaire method has been used in similar patient populations to ascertain patient knowledge of infection and its prevention. 10 17 The questionnaires were a cost-effective method that would assess our outcome measures with minimal disruption of clinical flow. The questionnaires also provided anonymity, particularly important for questions regarding satisfaction.…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations